2012
DOI: 10.1021/jm301019w
|View full text |Cite
|
Sign up to set email alerts
|

Shooting for Selective Druglike G-Quadruplex Binders: Evidence for Telomeric DNA Damage and Tumor Cell Death

Abstract: Targeting of DNA secondary structures, such as G-quadruplexes, is now considered an appealing opportunity for drug intervention in anticancer therapy. So far, efforts made in the discovery of chemotypes able to target G-quadruplexes mainly succeeded in the identification of a number of polyaromatic compounds featuring end-stacking binding properties. Against this general trend, we were persuaded that the G-quadruplex grooves can recognize molecular entities with better drug-like and selectivity properties. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 46 publications
(64 reference statements)
1
40
0
Order By: Relevance
“…Several different classes of ligands that target G4 DNA have been developed (Granzhan et al, 2010; Monchaud et al, 2010; Ohnmacht and Neidle, 2014). A number of these have been identified by our research group and most of them were discovered in order to target the grooves of the G4 structures (Cosconati et al, 2009, 2010, 2012; Pagano et al, 2010; Petraccone et al, 2011; Di Leva et al, 2013). On the other hand, several other research groups have developed molecules characterized by an extended planar aromatic scaffold, which is generally able to stack on the external G-tetrads of the G4.…”
Section: Introductionmentioning
confidence: 99%
“…Several different classes of ligands that target G4 DNA have been developed (Granzhan et al, 2010; Monchaud et al, 2010; Ohnmacht and Neidle, 2014). A number of these have been identified by our research group and most of them were discovered in order to target the grooves of the G4 structures (Cosconati et al, 2009, 2010, 2012; Pagano et al, 2010; Petraccone et al, 2011; Di Leva et al, 2013). On the other hand, several other research groups have developed molecules characterized by an extended planar aromatic scaffold, which is generally able to stack on the external G-tetrads of the G4.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking calculations on duplex DNA were performed using the structure of the B-DNA dodecamer [d(CGCGAATTCGCG)] 2 (PDB code: 1bna) (57), which has been reported to be recognized by 1 (42). …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, isothermal titration calorimetry (ITC) experiments showed that 1 binds to [d(TGGGGT)] 4 more tightly than distamycin A (41), that is the reference compound among the G-quadruplex groove binders. These biophysical experiments have been complemented by in vitro assays showing that 1 is able to induce DNA damage and cell-cycle arrest in specific cancer cell lines (42). …”
Section: Introductionmentioning
confidence: 99%
“…The small molecule pyridostatin, a very good stabilizer of the telomeric G-quadruplex with high selectivity over duplex DNA in vitro, also uncaps POT1 from human telomeres and triggers a DNA damage response [69]. A plethora of synthetic small molecules, synthetically more accessible than telomestatin, have high G-quadruplex affinity including the telomeric G-quadruplex (some are presented in [70][71][72][73][74][75][76]). A study using pyridostatin with a biotin affinity tag (FIGURE 4A & 4B) showed that telomeric DNA can be isolated from cells with a G-quadruplex interacting small molecule [16], and treating cultured cells with pyridostatin or some of its analogs leads to telomere shortening and senescence [16,77].…”
Section: Abstract: Chromatin • Dna Damage • G-quadruplex • Nucleic Acmentioning
confidence: 99%